Response and resilience of the microbial methane filter to ecosystem changes in Arctic peatlands - Rainer, Edda Marie (UiT The Arctic University of Norway, 2022)
Climate change is a major concern in the Arctic region, as large amounts of organic carbon (C) are stored in permafrost soils and sediments. Increasing average temperatures have the potential to release that C and making it available to biologic activity. Carbon-rich, anoxic soils such as peatlands are inhabited by methanogenic archaea that can metabolize by-products of microbial C decomposition and consequently release methane (CH 4 ). Methane oxidizing bacteria (MOB) comprise a major biological filter for CH 4 in terrestrial and aquatic ecosystems and thereby regulate CH 4 emissions to the atmosphere. The genus Methylobacter has been detected in many CH 4 rich ecosystems and several circumpolar locations. Climate change in the Arctic includes changes in both temperature and precipitation as well as ecosystem changes related to plant cover and herbivory. All of these changes have the potential to influence soil structure and soil biological processes. Thus, they are important factors controlling the soil C cycle and eventually the activity of MOB. The aim of this thesis was to investigate the ability of the Arctic biological CH 4 filter to adapt to changes in vegetation, CH 4 concentrations and temperature. Further, to gain insights in the resilience and resistance of the MOB community to environmental changes. We have shown that herbivory by geese changes the soil structure and thus the vertical distribution of CH 4 and oxygen (O 2 ) concentrations in a high Arctic peatland. These differences are accompanied by changes in the potential rates of CH 4 oxidation. The highest activity was detected in shallower parts of the peatland in grazed sites compared to sites protected from grazing. Different MOB communities are responsible for the CH 4 oxidation, depending on the above ground grazing and these communities are composed of closely related Methylobacter OTUs. Exposing peat soils from both grazed and protected sites to increased CH 4 concentrations and temperature revealed that MOB respond strongly to changing ...